2020
DOI: 10.1016/j.heliyon.2020.e03619
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of antifungal resistant Candida africana, in the C. albicans complex causing vulvovaginal candidiasis

Abstract: The Candida (C.) albicans complex includes C. albicans, C. dubliniensis, C. stellatoidea, and C. africana, with the last mentioned as an important emerging agent of vulvovaginal candidiasis (VVC). The aim of the study was to identify C. africana and C. dubliniensis and assess their drug susceptibility in vaginitis. One-hundred Candida isolates of the C. albicans complex from women diagnosed with vaginitis and from vaginal samples in the culture collection of a medical mycology laboratory were examined. Species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
5
16
1
Order By: Relevance
“…Contrary to our findings, other studies that attempted to identify the cryptic species of C. albicans complex were able to identify, in addition to C. albicans , only C. africana [10] , [16] , [28] or C. dubliniensis [11] , [27] . Interestingly, Gumral et al , evaluated vaginal Candida isolates using HWP1 gene polymorphism and found neither C. dubliniensis nor C. africana among the C .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, other studies that attempted to identify the cryptic species of C. albicans complex were able to identify, in addition to C. albicans , only C. africana [10] , [16] , [28] or C. dubliniensis [11] , [27] . Interestingly, Gumral et al , evaluated vaginal Candida isolates using HWP1 gene polymorphism and found neither C. dubliniensis nor C. africana among the C .…”
Section: Discussioncontrasting
confidence: 99%
“…We found in our investigation that C. africana has a higher isolation rate (5.13%) than the C. dubliniensis (0.64%). This result corroborates the findings reported in Iran-where the frequency C. africana (3%) and C. dubliniensis (0%) was reported among 100 vaginal isolates of C. albicans species complex [10] –and a multicenter study that reported a higher frequency of C. africana (7.2%) than C. dubliniensis (2.9%), among Candida isolates recovered from 498 clinical specimens originated from various patient groups [26] . However, the higher isolation rate of C. dubliniensis over C. africana is being reported from other studies [9] , [13] , [19] , [20] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, there are reports in which isolates of C . africana have been categorized as resistant to itraconazole, 5-flucytosine, terbinafine, fluconazole, and clotrimazole [ 28 , 33 , 54 ]. By applying the clinical breakpoints for C .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study recorded the presence of some yeast species in shrimp M. amazonicum, concluding that the genus may be part of the microbiota of crustaceans (Brilhante et al, 2014). Infection by Candida in humans can result in mucocutaneous and systemic diseases in immunosuppressed hosts when the infectious load is high, despite being considered a commensal of the skin and gastrointestinal tract (Maranhão et al, 2019;Farahyar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%